(untitled) (Journal of Hama University, 2026)
Fadl was one of the figures who represented the faces of al-Mutawakkil’s councils and companions during the second Abbasid era. Fadl received considerable attention—of varying size and value—from biographers, historians, and writers, and occupied a significant space in the writings of her contemporaries, including narrators and historians. This was not only because she was the most poetic woman of her time; Rather, it was due to her connection to Al-Mutawakkil, his days, and her poems therein. These scattered spaces in the books of ancient literature and its sources were the merit of completing this research on a female figure who had an important artistic presence in the court of Al-Mutawakkil. She was the most distinguished poet of her time, and her poems that she said in the court were historical documents chronicling an era of time, and describing the legendary scenes of luxury, comfort, and extravagance that historians were unable to describe. So, she had no choice but to join the poets of the palace and the caliph’s concubines and be a pearl of this unique and organized necklace, and her biography would be an image of the companions of the first caliph in the second Abbasid era, Al-Mutawakkil, and to see - in her capacity as a concubine of Al-Mutawakkil - his luxurious palaces and his luxurious lifestyle. Her poems expressed the artistic taste that was prevalent at that time, and her news depicted scenes of the councils of Poetry in the Caliphate’s Court.The research aims to shed light on a poet considered one of the most important poets at the court of Caliph al-Mutawakkil. It discusses her personal and professional life, cites examples of her poems composed for al-Mutawakkil, and discusses her literary status and poetic standing, as well as how this poet was able to occupy significant spaces in ancient literary books and sources.The research problem and its questions revolve around the artistic value of Fadl al-Abdiyya’s poetry, the importance of her poems that commemorated important political occasions, such as al-Mutawakkil’s accession to the caliphate, and her descriptions of the events of her time in poems that constitute historical documents worthy of